Mild traumatic brain injury in the United States: demographics, brain imaging procedures, health-care utilization and costs. (29th July 2019) - Pavlov, Vladislav; Thompson-Leduc, Philippe; Zimmer, Louise; Wen, Jody; Shea, Jerome; Beyhaghi, Hadi; Toback, Seth; Kirson, Noam; Miller, Mark
ABSTRACT: Objective : To characterize mild traumatic brain injury (mTBI) patients in the USA, describing location of diagnosis, timing, and modality of imaging procedures, health-care resource utilization (HRU) and costs in the 12-month period post-diagnosis. Research Design : Retrospective claims analysis Methods : Anonymized data from the OptumHealth Care Solutions claims database (2006–2016). The index date was the first date with an mTBI diagnosis. HRU and costs (2016 USD) were assessed in the 12-month post-index period. Results : A total of 80, 004 patients with mTBI were included: 60% were under 26 years and 54% were male. Mild TBI was most frequently diagnosed in an emergency department (ED) for all age groups, except patients aged 11–17 years, for whom the outpatient setting was the most frequent place of diagnosis. Almost half (47%) received brain imaging on the index date, with 98% of which receiving computed tomography. Mean follow-up health-care costs were $13, 564 (SD = $41, 071), primarily from inpatient ($4, 675, SD = $29, 982) and non-ED outpatient/physician office visits ($4, 207, SD = $12, 697). Older patients had greater HRU and higher health-care costs. Conclusions : The findings of this claims-based study show substantial HRU and costs associated with mTBI diagnosis during a 12-month follow-up period.